Pengaruh Shift Kerja Terhadap Kelelahan dan Performansi Pengendali Kereta Api Indonesia - Lauditta Irianti (Jurnal Rekayasa Sistem Industri, 2017)
The purpose of this study is  to evaluate the effect of shift work on level of fatigue and  performance of railway controller. Seventeen participants are the railway controller of Bandung Station. Fatigue was measured using subjective questionaire Swedish Occupational Fatigue Inventory (SOFI) and performance was measured using Psychomotor Vigilance Task based on reaction time.  Friedman test and Bonferonni-Dunn test were used to process data. Statistical analysis indicates there was significant difference level of fatigue and human performance between shift work. Fatigue occurs at sleepiness, phsysical discomfort and lack of motivation dimensions, while performance occurs at mean 1/RT, fastest 1/RT and slowest 1/RT (P < 0,10). %. The highest fatigue and the worst performance occurs after night shift. After night shift, the level of fatigue increased about 37% to 162%, meanwhile performance were decreased about 3% to 11%. Although there were significant difference of level fatigue, the average scores are below 1 (score 0-7). This result indicates that the fatigue of controllers  are very low.  Although maybe is not really necessary to redesign shift work system, but working hours on each shift still need to be concerned.